ANALYSIS OF THE COMPETITIVENESS OF GLOBAL AGRICULTURAL MARKETS: ANALYTICAL HIERARCHY PROCESS - Chen Lei (American Journals Publishing, 2023)
With the increase in agricultural production and food consumption simultaneously, global markets are increasingly targeting the highest quality and healthiest agricultural products. Therefore, it is essential to understand nature of the global markets and to produce better by being competitive so that companies can manage high risk and increase profitability effectively. This study aims to analyze the competitiveness of global agricultural markets based on the analytical hierarchy process and the factors on which the competitiveness depends. To identify the most relevant factors that contribute to the competitiveness of global agricultural markets in relation to several global agricultural markets, stakeholder interviews and literature review are implemented. To attain the study objective, based on the data retrieved from stakeholder interview and literature review, we calculated the highest weights of relative importance of the factors to show ranking of success criteria and determined the export priority and competitiveness methodology of agricultural companies in global markets. The methodological tools proposed in the study can be used as a guideline of monitoring the development of market strategies and programs for the improvement of export-oriented agricultural sectors in the countries like Uzbekistan where agricultural production contributes to higher economic development. Also, the results of applying the proposed approach in the performance case of real firms showed that agricultural production is profitable from both a financial and economic perspectives since they have an optimal competitiveness strategy. Finally, the paper ends with theoretical and practical implications as well as future research agenda.
Keywords: Analytical Hierarchy Process, Global Agricultural Markets, Decision Criteria, Stakeholder Interview